2020
DOI: 10.1038/s41401-020-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

β-sitosterol ameliorates influenza A virus-induced proinflammatory response and acute lung injury in mice by disrupting the cross-talk between RIG-I and IFN/STAT signaling

Abstract: β-Sitosterol (24-ethyl-5-cholestene-3-ol) is a common phytosterol Chinese medical plants that has been shown to possess antioxidant and anti-inflammatory activity. In this study we investigated the effects of β-sitosterol on influenza virus-induced inflammation and acute lung injury and the molecular mechanisms. We demonstrate that β-sitosterol (150-450 μg/mL) dosedependently suppresses inflammatory response through NF-κB and p38 mitogen-activated protein kinase (MAPK) signaling in influenza A virus (IAV)-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 88 publications
(111 reference statements)
1
34
0
Order By: Relevance
“…The mechanism may be related to the targeting of NETs through NADPH/ROS network signaling [70] . β-sitosterol exhibited a dose-dependent inhibition of in ammatory responses in in uenza A virus -infected cells via NF-κB and p38MAPK signaling [71] .…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism may be related to the targeting of NETs through NADPH/ROS network signaling [70] . β-sitosterol exhibited a dose-dependent inhibition of in ammatory responses in in uenza A virus -infected cells via NF-κB and p38MAPK signaling [71] .…”
Section: Discussionmentioning
confidence: 96%
“…Li et al reported that β-sitosterol is a candidate for the development of anti-virulence agents against pathogens that rely on cholesterol-dependent toxins for successful infections [25]. Zhou et al reported that β-sitosterol blocks the immune response mediated by RIG-I signaling and deleterious IFN production, providing a potential benefit for the treatment of influenza [26]. Parvez et.…”
Section: β-Sitosterol As Immunostimulant As Antiviral and As Antioxidantmentioning
confidence: 99%
“…Nonetheless, the decrease in markers of inflammation might be a side effect of the cholesterol reduction. The influence of -sitosterol (Figure 3), the most abundant form in human serum (about 6 m), on inflammation caused by influenza A virus (IAV) infection was recently reported by Zhou et al [73].…”
Section: Cholesterol Reduction By Statins As Antiviral Treatmentmentioning
confidence: 70%